2011
DOI: 10.1121/1.3621119
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective muffler shape optimization with hybrid acoustics modeling

Abstract: This paper considers the combined use of a hybrid numerical method for the modeling of acoustic mufflers and a genetic algorithm for multiobjective optimization. The hybrid numerical method provides accurate modeling of sound propagation in uniform waveguides with non-uniform obstructions. It is based on coupling a wave based modal solution in the uniform sections of the waveguide to a finite element solution in the non-uniform component. Finite element method provides flexible modeling of complicated geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…However, the methods proposed on the basis of these investigations can be mainly applied to concentric expansion chamber mufflers, and the obtained optimal mufflers cannot avoid extreme pressure drops, caused by high flow resistance. The work by Airaksinen and Heikkola optimized nonconcentric mufflers, but it did not consider pressure drops. The drawbacks of the previous researches are due to two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…However, the methods proposed on the basis of these investigations can be mainly applied to concentric expansion chamber mufflers, and the obtained optimal mufflers cannot avoid extreme pressure drops, caused by high flow resistance. The work by Airaksinen and Heikkola optimized nonconcentric mufflers, but it did not consider pressure drops. The drawbacks of the previous researches are due to two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 Airaksinen, et al 12 provided a combined use of a hybrid finite method and genetic algorithm for the multi-objective optimization of various mufflers. However, these optimizations are either limited in use or computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The configuration studied in this section is the first of those shown in Table 3. 4. The temperatures used to compute the corresponding fields, following the scheme of Figure 3.3, are shown in Table 3.…”
Section: Variable Temperature Fieldmentioning
confidence: 99%
“…The configurations of the silencer under study are geometries 1 and 3 of those shown in Table 3. 4. Two extra computations have been carried out for comparison purposes considering geometry 1.…”
Section: Silencers Incorporating Sintered Ductsmentioning
confidence: 99%
See 1 more Smart Citation